2013
DOI: 10.1088/1742-5468/2013/02/p02038
|View full text |Cite
|
Sign up to set email alerts
|

From creeping to inertial flow in porous media: a lattice Boltzmann–finite element study

Abstract: The lattice Boltzmann method has been successfully applied for the simulation of flow through porous media in the creeping regime. Its technical properties, namely discretization, straightforward implementation and parallelization, are responsible for its popularity. However, flow through porous media is not restricted to near zero Reynolds numbers since inertial effects play a role in numerous natural and industrial processes. In this paper we investigate the capability of the lattice Boltzmann method to corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…It is commonly being reported that the Forchheimer equation consistently overestimates pressure gradients in the so‐called weak inertia regime scriptO(101)<Re<scriptO(101), where R e is based on the average velocity and a microscopic length scale depending, e.g., on the grain size. In particular, various numerical [e.g., Narváez et al , ; Rojas and Koplik , ; Andrade et al , ; Firdaouss et al , ; Mei and Auriault , ] as well as experimental studies [e.g., Skjetne and Auriault , ; Lage et al , ] articulate the use of a leading cubic term in the weak inertia regime in the form of J1cX1Pϱg=μκq1ϱ2ζμq13, with ζ being a material‐dependent fitting coefficient. Others have used nonconstant Forchheimer coefficients c F = c F ( q ) to account for higher‐order contributions [e.g., Chukwudozie and Tyagi , ; Mattis et al , ].…”
Section: Motivationmentioning
confidence: 99%
“…It is commonly being reported that the Forchheimer equation consistently overestimates pressure gradients in the so‐called weak inertia regime scriptO(101)<Re<scriptO(101), where R e is based on the average velocity and a microscopic length scale depending, e.g., on the grain size. In particular, various numerical [e.g., Narváez et al , ; Rojas and Koplik , ; Andrade et al , ; Firdaouss et al , ; Mei and Auriault , ] as well as experimental studies [e.g., Skjetne and Auriault , ; Lage et al , ] articulate the use of a leading cubic term in the weak inertia regime in the form of J1cX1Pϱg=μκq1ϱ2ζμq13, with ζ being a material‐dependent fitting coefficient. Others have used nonconstant Forchheimer coefficients c F = c F ( q ) to account for higher‐order contributions [e.g., Chukwudozie and Tyagi , ; Mattis et al , ].…”
Section: Motivationmentioning
confidence: 99%
“…We follow the procedure to measure permeabilities as described in Narváez et al [28,29], Frijters [30] and Frijters and Harting [31]. The LB method itself has proven to be very successful for modeling fluid flow in porous media [32].…”
Section: The Lattice Boltzmann Methodsmentioning
confidence: 99%
“…[29,34]. Narváez et al [28,29] have shown that relaxation times of τ = 1 and τ bulk = 0.84 provide useful results for permeability calculations. The porous sample is positioned between two fluid chambers which serve as in-and output to avoid artifacts, cf.…”
Section: The Lattice Boltzmann Methodsmentioning
confidence: 99%
“…Here simulations of the complex fluid-fluid and fluid-rock interfaces are also needed to gain further insight [40,41,42].…”
Section: Big Data For World-wide and Multiscale Problemsmentioning
confidence: 99%